2005
DOI: 10.1152/ajpendo.00317.2004
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone secretion in primary adrenal Cushing's syndrome is disorderly and inversely correlated with body mass index

Abstract: . Growth hormone secretion in primary adrenal Cushing's syndrome is disorderly and inversely correlated with body mass index. Am J Physiol Endocrinol Metab 288: E63-E70, 2005. First published August 24, 2004; doi:10.1152/ajpendo.00317.2004.-To evaluate the impact on the somatotropic axis of endogenous cortisol excess in the absence of primary pituitary disease, we investigated spontaneous 24-h growth hormone (GH) secretion in 12 adult patients with ACTH-independent hypercortisolism. Plasma GH concentration pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…ApEn quantities the orderliness of the subordinate (ϭ nonpul- satile) secretory GH patterns. A larger GH ApEn value denotes greater irregularity and has been reported during puberty and in patients with acromegaly and Cushing's disease (41,48). Decreased regularity could reflect impaired coordinate control of GH secretion by GH-releasing hormone (GHRH), somatostatin, GH, and/or IGF-I.…”
Section: Discussionmentioning
confidence: 98%
“…ApEn quantities the orderliness of the subordinate (ϭ nonpul- satile) secretory GH patterns. A larger GH ApEn value denotes greater irregularity and has been reported during puberty and in patients with acromegaly and Cushing's disease (41,48). Decreased regularity could reflect impaired coordinate control of GH secretion by GH-releasing hormone (GHRH), somatostatin, GH, and/or IGF-I.…”
Section: Discussionmentioning
confidence: 98%
“…A referral bias leading to increased 7 7 prevalence of non-pituitary CS in our institution may explain this difference in clinical presentation. While pure cortisol-secreting pituitary CD would inhibit growth (cortisol suppresses GH production [37], combined with a possible pituitary mass effect leading to GH deficiency), adrenal CS tumors cosecreting androgens would promote growth and hence stature would be less affected. In a previous series of 72 children with CD, growth retardation was present in 82%, hypertension in 46% and striae in 40% [2].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the KIMS database showed that GH deficient (GHD) patients with a previous history of CD had the same characteristics in terms of body composition and lipid levels but a higher prevalence of diabetes, hypertension, bone fractures and lower BMD, as well as a more impaired quality of life compared to GHD patients with other aetiologies (148). As GCs significantly impact on adiposity and BMI, which in turn can affect GH secretion, BMI alone can only partially explain GH impairment in CS patients (149).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%